FAKTOR-FAKTOR DETERMINAN DALAM PENETAPAN BESARAN GAJI PEGAWAI PADA PERUSAHAAN SWASTA - Janry Haposan U. P. Simanungkalit (Widyariset, 2009)
In determining or establishing workers' salary/wage, one of the main problems faced by company/firm is what factors or components that form to determine salary, notably in private company. The objectives of this study are: (1) to analyze and explain workers' salary conditions in private company now (existing) and (2) to anaylze and explain salary structure that form on private company. This study uses primary data collected from respondents through observation using research instrument based on variables, i.e. dependent variable, namely employ salary per month from main job/work (Y) and 6 (six) independent variables, namely working life (X), gender (X), marital status (X), education level (X), type of job (X), and productivity level of employ N Multiple regression method was used to analyze the data with SPSS version 11.5 software. The results of the study show that working life employ, education level, and type of job are influential significantly to employ salary. Meanwhile gender, marital status, and productivity level of employ are not influential significantly to employ salary.